Complex immunohistochemical and molecular study on 5 cases of ovarian juvenile granulosa cell tumors reveals a consistent alteration in the PI3K/AKT/mTOR signaling pathway - Adam Šafanda; Nikola Hájková; Michaela Kendall Bártů; Marián Švajdler; Radoslav Matěj; Jitka Hausnerová; Tomáš Zima; Pavel Dundr; Kristýna Němejcová (Diagnostic Pathology)
Abstract Background Juvenile granulosa cell tumor (JGCT) of the ovary is a rare tumor with distinct clinicopathological and hormonal features primarily affecting young women and children. We conducted a complex clinicopathological, immunohistochemical, and molecular analysis of five cases of JGCT. Methods The immunohistochemical examination was performed with 32 markers, including markers that have not been previously investigated. Moreover, DNA next-generation sequencing (NGS) and PTEN methylation analysis was performed. Result We found the expression of calretinin, inhibin A, SF1, FOXL2, CD99, CKAE1/3, ER, PR, AR in all cases. WT1 was expressed in one case. Conversely, the expression of p16, OCT3/4, SALL4, GATA3, Napsin A, SATB2, MUC4, TTF1, and CAIX was completely negative. All tumors showed the wild-type pattern of p53 expression. Regarding predictive markers, all tumors were HER2 negative and did not express PD-L1. Mismatch repair proteins (MMR) showed no loss or restriction of expression, similarly to ARID1A, DPC4, BRG1, and INI1. The molecular analysis revealed AKT1 internal tandem duplication in two tumors. Two other cases exhibited mutations in TERT and EP400 and both developed recurrence. All AKT1-wild type tumors exhibited immunohistochemical loss of PTEN expression. However, no mutations, deletions (as assessed by CNV analysis), or promoter hypermethylation in the PTEN gene were detected. Conclusion The results of our study further support the hypothesis that the pathogenesis of JGCT may be driven by activation of the PIK3/AKT/mTOR pathway. These findings could potentially have future therapeutic implications, as treatment strategies targeting the PTEN/mTOR pathways are currently under investigation.